I'm Not the Man I Was: Reflections on Becoming a Widower. (January 2013) - Howell, Robert
The death of one's wife plunges the surviving husband into confusing, terrifying, isolating and heart rending feelings and experiences as he tries to make sense of something that makes no sense. The experience raises questions about the relationship between loss and grief; emerging meanings and transitions in identity. This author reflects on his own experience of being widowed and shares some of the insights of others he has worked with in grief support programs. This article focuses on the intertwined questions of profound loss, the search for meaning and the impact of that search on the reshaping of identities.